THE CRITERIA, INDEXES AND LEVELS OF TEACHER'S OF NATURAL AND MATHEMATICS SUBJECTS INFORMATION COMPETENCE DEVELOPMENT - Petro Grabovskiy (Kherson State University, 2015)
Submitted research depends on an actual problem - how is necessary to identify means of teacher's of general education information competence evaluation. In particular, there developed on an evaluation criteria of teacher's of Natural and Mathematics subjects information competence - motivational, cognitive-operating, reflexive; and decomposition to appropriated performance criterion made in this research too. With the help of empirical research methods, in particular the method of expert evaluations, using methods of relative frequency selection, determing by an expert's performance and relevant criteria, proved significance when evaluation of teacher's of Natural and Mathematics subjects information competence development is appropriated. Based on the grounded and developed criteria and relevant indicators where four levels of studing teacher's information competence development were describing - low, middle, sufficient and high levels. According to an author opinion, the further research may be concern with the help of mathematical tools development to determine the level of teacher's of Natural and Mathematics subjects information competence development based on the selected criteria and relevant indicators